Improvement of DEP Cell Sorter by Design of Flow Channel for Higher Field Gradient. Issue 2 (February 2014) - Suzuki, Seiichi; Ito, Emiko; Hasegawa, Sena; Takahashi, Tsutomu; Hara, Takahiko
Summary In this study, high separation ratio microfluidic cell sorting by a dielectrophoretic (DEP) force is presented. The recent development of iPS cell technology has raised the possibility of regenerative therapy. Technologies of genetic cell processing require purification of specific target cells by a cell sorter. The most widely used system for cell separation is flow cytometry (FCM), which has been developed for research purposes. Despite the excellent separation ratio it achieves, it has a rather high cost per operation. For clinical use, devices contacting biological specimens must be disposable to prevent cross‐infection. A low cost microfluidic cell sorter, using the DEP force, can be fabricated by photolithography. However, the sorting rate of existing DEP cell sorters is far lower than that of FCM because of limitations of the applicable voltage in an aqueous fluid. To circumvent the problem and raise the DEP force, the implementation of field gradient dependence was investigated. The flow channel was designed to produce a high gradient at the separation point and to enhance the DEP force. Numerical calculations by the finite element method indicate that the electric field distribution has a peak intensity at the entrance to the separation channel. DEP separation of latex beads 2 <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg4sn4smr9" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />μ</alternatives>m in diameter at a flow speed of 3.0 mm/s, six times that of our previous system, was demonstrated.